Pulmonary epithelial barrier and immunological functions at birth and in early life - key determinants of the development of asthma? A description of the protocol for the Breathing Together study [version 1; peer review: 2 approved] - Turner,S; Custovic,A; Ghazal,P; Grigg,J; Gore,M; Henderson,J; Lloyd,C; Marsland,B; Power,U; Roberts,G; Saglani,S; Schwarze,J; et al. (Wellcome Open Research, 2018)
Background. Childhood asthma is a common complex condition whose aetiology is thought to involve gene-environment interactions in early life occurring at the airway epithelium, associated with immune dysmaturation. It is not clear if abnormal airway epithelium cell (AEC) and cellular immune system functions associated with asthma are primary or secondary. To explore this, we will (i) recruit a birth cohort and observe the evolution of respiratory symptoms; (ii) recruit children with and without asthma symptoms; and (iii) use existing data from children in established STELAR birth cohorts. Novel pathways identified in the birth cohort will be sought in the children with established disease. Our over-arching hypothesis is that epithelium function is abnormal at birth in babies who subsequently develop asthma and progression is driven by abnormal interactions between the epithelium, genetic factors, the developing immune system, and the microbiome in the first years of life.Methods. One thousand babies will be recruited and nasal AEC collected at 5-10 days after birth for culture. Transcriptomes in AEC and blood leukocytes and the upper airway microbiome will be determined in babies and again at one and three years of age. In a subset of 100 individuals, AEC transcriptomes and microbiomes will also be assessed at three and six months. Individuals will be assigned a wheeze category at age three years. In a cross sectional study, 300 asthmatic and healthy children aged 1 to 16 years will have nasal and bronchial AEC collected for culture and transcriptome analysis, leukocyte transcriptome analysis, and upper and lower airway microbiomes ascertained. Genetic variants associated with asthma symptoms will be confirmed in the STELAR cohorts. Conclusions. This study is the first to comprehensively study the temporal relationship between aberrant AEC and immune cell function and asthma symptoms in the context of early gene-microbiome interactions.